Circulation of modified Circumpolar Deep Water and basal melt beneath the Amery Ice Shelf, East Antarctica. Issue 4 (26th April 2015) - Herraiz‐Borreguero, Laura; Coleman, Richard; Allison, Ian; Rintoul, Stephen R.; Craven, Mike; Williams, Guy D.
Abstract Antarctic ice sheet mass loss has been linked to an increase in oceanic heat supply, which enhances basal melt and thinning of ice shelves. Here we detail the interaction of modified Circumpolar Deep Water (mCDW) with the Amery Ice Shelf, the largest ice shelf in East Antarctica, and provide the first estimates of basal melting due to mCDW. We use subice shelf ocean observations from a borehole site (AM02) situated ∼70 km inshore of the ice shelf front, together with open ocean observations in Prydz Bay. We find that mCDW transport into the cavity is about 0.22 ± 0.06 Sv (1 Sv = 106 m3 s−1). The inflow of mCDW drives a net basal melt rate of up to 2 ± 0.5 m yr−1 during 2001 (23.9 ± 6.52 Gt yr−1 from under about 12, 800 km2 of the north‐eastern flank of the ice shelf). The heat content flux by mCDW at AM02 shows high intra‐annual variability (up to 40%). Our results suggest two main modes of subice shelf circulation and basal melt regimes: (1) the "ice pump"/high salinity shelf water circulation, on the western flank and (2) the mCDW meltwater‐driven circulation in conjunction with the "ice pump, " on the eastern flank. These results highlight the sensitivity of the Amery's basal melting to changes in mCDW inflow. Improved understanding of such ice shelf‐ocean interaction is crucial to refining projections of mass loss and associated sea level rise.